Empagliflozin attenuates ventricular fibrillation postmyocardial infarction associated with reduced transforming growth factor-1/Smad3 signaling and miR-181a expression - Jingsong Shen; Min Huang; Zixu Ye; Yuling Jing; Ziyang Yuan; Zeming Xiang; Miao Ding; Tao Li; Qiang Ye (Journal of International Medical Research, 2025)
Objective To determine whether empagliflozin reduces ventricular fibrillation and myocardial fibrosis after myocardial infarction via the transforming growth factor-β1/Smad3/miR-181a pathway. Methods Male nondiabetic Sprague–Dawley rats (n = 16) were randomized into sham, myocardial infarction, low-dose empagliflozin (10 mg/kg/day), and high-dose empagliflozin (30 mg/kg/day) groups. Myocardial infarction was induced via coronary artery ligation. After 4 weeks, ventricular fibrillation thresholds were assessed via electrical stimulation. Cardiac function (echocardiography), fibrosis (Masson’s trichrome staining), and molecular markers (transforming growth factor-β1, Smad3, miR-181a; assessed via western blotting/quantitative polymerase chain reaction) were analyzed. Results Empagliflozin-treated groups showed reduced left ventricular dilation (left ventricular internal diameters at end-diastole: 8.2 ± 0.3 vs. 9.1 ± 0.4 mm in myocardial infarction; left ventricular internal diameters at end-systole: 5.1 ± 0.2 vs. 6.0 ± 0.3 mm) and improved ejection fraction (45% vs. 38% in myocardial infarction). Ventricular fibrillation thresholds increased significantly with empagliflozin administration (p < 0.05). Myocardial fibrosis (collagen volume fraction: 12% vs. 25% in myocardial infarction) and transforming growth factor-β1/Smad3/miR-181a expression were downregulated in empagliflozin groups (p < 0.01). No dose-dependent differences were observed between the groups. Conclusions Empagliflozin attenuates postmyocardial infarction ventricular arrhythmias and fibrosis associated with the suppression of transforming growth factor-β1/Smad3 signaling and miR-181a expression, enhancing cardiac function. These findings highlight its therapeutic potential in postinfarct remodeling.